A Five-Year Followup of Human Seminal Plasma Allergy in an 18-Year-Old Woman - Ole D. Wolthers (Case Reports in Medicine)
Case reports of women with the rare condition of human seminal plasma allergy have indicated that the condition may be associated with life-threatening anaphylactic reactions in relation to coitus. Few observations, if any, of long-term outcome of the condition are available. The aim of this paper was to present a case diagnosed in an 18-year-old girl who presented with generalized urticaria, nasal congestion and secretion, conjunctivitis, and periorbital and labial oedema 6–8 hours after coitus. During five years of followup the condition improved clinically significantly. Due to intimacy concerns and the low prevalence of the condition robust long term data on the natural course of the condition are difficult to obtain. The present case suggests that in some patients the condition may improve over time.